HEADDRESSES OF THE BUKHARIANS AND THE FEATURES OF THE ART OF GOLDEN EMBROIDERY ON THEM - Norova D. R. (TARIXIY TADQIQOTLAR, 2026)
The article explores the types of men’s and women’s headdresses and highlights how the art of gold embroidery is reflected in their design. Particular attention is given to Muslim headwear, its long-standing use among local communities, and its significance within cultural and religious traditions.